POLÍTICAS PÚBLICAS PARA O URBANO EM GUARAPUAVA/PR: INTERESSES E INTERVENÇÕES - PRUDENTES, TATIELLEN CRISTINA (2017)
The objective of this dissertation was to analyze shapes of urban intervention from public policies, with funding from the federal government, in the city of Guarapuava/PR, with the temporal clipping of 2013 to 2016. The research was implemented in three steps. In the first, focused on the literature review to discuss the concepts and issues facing the public policies; in the second stage, the studies were concentrated in the collections and analyzes of data from secondary sources, extracted from governmental and non-governmental institutions in Brazil and interviews. In the third step, it describes the covenant established between the federal government and the local government, the city of Guarapuava, in terms of public policy intervention for the urban space, approved in the period 2013 to 2016. At this stage, are analyzed two examples among all public policies urban period, that is, the reurbanization of Rua XV de Novembro and the program of land regularization Papel Passado, in addition to the scenario of interests and intervention relating to these public policies in Guarapuava. It is concluded that in Guarapuava, the political factors intermediate, the distribution of public policies. An intervention by means of political actions with the purpose of promotion, enhancement, perpetuation of a group of power, composed of intention and speeches, which are driven by interests and conflicts, conducted by groups of family power, that emphasize their political alignments and partisan.